2007
DOI: 10.1103/physrevlett.98.145504
|View full text |Cite
|
Sign up to set email alerts
|

Fano Lineshape and Phonon Softening in Single Isolated Metallic Carbon Nanotubes

Abstract: Evolution of G-band modes of single metallic carbon nanotubes with the Fermi level shift is examined by simultaneous Raman and electron transport studies. Narrow Lorentzian line shape and upshifted frequencies are observed near the van Hove singularities. However, all G modes soften and broaden at the band crossing point. The concurrent appearance of an asymmetric Fano line shape at this point indicates that phonon-continuum coupling is intrinsic to single metallic tubes. The apparent Lorentzian line shapes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
119
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(153 citation statements)
references
References 28 publications
29
119
3
1
Order By: Relevance
“…27,87,91,[137][138][139][140] The absence of the LO phonon feature for armchair tubes is consistent with some theoretical studies (e.g., References 27 and 145), i.e., it is not Raman active in armchair SWCNTs (although this still does not eliminate the presence of a Kohn anomalyonly its Raman activity), while it is inconsistent with more recent theories. 90,146 In conclusion, using resonant Raman measurements of macroscopic ensembles of ν = 0 enriched SWCNT samples, we have demonstrated that the appearance of a broad G − peak is due to the presence of non-armchair "metallic" tubes.…”
Section: G-band Raman Signatures Of Armchair and Non-armchair ν supporting
confidence: 39%
See 2 more Smart Citations
“…27,87,91,[137][138][139][140] The absence of the LO phonon feature for armchair tubes is consistent with some theoretical studies (e.g., References 27 and 145), i.e., it is not Raman active in armchair SWCNTs (although this still does not eliminate the presence of a Kohn anomalyonly its Raman activity), while it is inconsistent with more recent theories. 90,146 In conclusion, using resonant Raman measurements of macroscopic ensembles of ν = 0 enriched SWCNT samples, we have demonstrated that the appearance of a broad G − peak is due to the presence of non-armchair "metallic" tubes.…”
Section: G-band Raman Signatures Of Armchair and Non-armchair ν supporting
confidence: 39%
“…Earlier theoretical studies described this broad feature as a Breit-Wigner-Fano line shape due to the coupling of phonons with an electronic continuum 81 or low-frequency plasmons, 136 but there is now growing consensus that the broad G − peak is a frequency-softened and broadened longitudinal optical (LO) phonon feature, a hallmark of Kohn anomalies. 27,87,91,[137][138][139][140] Through either scenario, this broad G − peak has conventionally been known to be a "metallic" feature, indicating the presence of metallic tubes.…”
Section: G-band Raman Signatures Of Armchair and Non-armchair ν mentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Recently, it has been shown that the frequencies and spectral widths of the ⌫ point optical phonons ͑called the G band in Raman spectra͒ depend on the position of the Fermi energy E F and the chirality of the metallic SWNT. [28][29][30][31] The Fermienergy dependence of the Raman spectra can be used to determine the position of the Fermi energy, and the chirality dependence of the Raman spectra provides detailed information on the electronic properties near the Fermi energy of metallic SWNTs. These dependences originate from the fact that the conduction electrons of a metal partly screen the electronic field of the ionic lattice.…”
Section: Introductionmentioning
confidence: 99%
“…В зависимо-сти от направления колебаний G-моды разделяют на продольные (LO) и поперечные (TO). Известно, что характерные особенности G-мод (профиль линии, часто-та, полуширина, относительная интенсивность) крайне чувствительны, с одной стороны, к собственным струк-турным параметром ОУНТ (диаметру d, хиральному углу θ, типу проводимости), а с другой стороны, к различным внешним воздействиям: к допированию [5], напряжению и давлению [6,7], и изменению в окруже-нии нанотрубки [8]. Следует отметить, что подробная информация о G-модах была получена в основном из измерений спектров КРС, выполненных на простран-ственно изолированных индивидуальных структурно-идентифицированных ОУНТ [9].…”
Section: Introductionunclassified